A Critical Assessment of Kleingeld - Bernasconi Debate On Kant’s Racism - Govedarica, Jelena; Smajević Roljić, Milica (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This paper offers a critical evaluation of the arguments that Kleingeld and Bernasconi used to support their claims regarding the idea that Kant held racist beliefs. Firstly, we will criticize the views on which they agree, aiming to emphasize our understanding of Kant’s thoughts on race. Secondly, we will assess the significance of Kant’s draft for Towards Perpetual Peace when considering the debate over Kant’s racism, and show that Bernasconi’s interpretation according to which Kant presented racist views in the third Critique and in his writings on history is problematic. Although we will not systematically present our understanding of Kant’s thoughts on race, our critique will reflect our basic views: Kant was not a racist, and he never advocated for slavery and colonization. Kleingeld is right to insist that we must interpret Kant’s thoughts on race diachronically, as it is clear that his views evolved but did not radically change.